Comparative life cycle assessment of uses of rice husk for energy purposes. - Prasara, Jittima
Purpose Recently, the Thai government has been advancing the expanded use of biomass as an alternative source of energy substituting it for the fossil fuels that have been shown to be harmful to the environment. Rice husk, one of the main sources of biomass in Thailand, has already been used as an energy source in many different applications and has been successful in reducing the consumption of fossil fuels. At present (2011), the main use of rice husk in Thailand is as fuel to generate electricity. However, rice husk can potentially be used to produce other forms of energy such as cellulosic ethanol. This paper compares the environmental performance of the current main use of rice husk for energy purposes in the Thai context, i.e., for electricity generation with the prospective use, i.e. for cellulosic ethanol production. The results from this study will identify the more environmentally friendly option for use of rice husk for energy purposes. Materials and methods To determine the more environmentally friendly rice husk use option, that being the option that showed the greatest reduction of environmental impacts, the environmental impacts of the two selected rice husk use options were compared with the environmental impacts of their conventional energy production processes using the life cycle assessment (LCA). The LCA software package SimaPro 7.1.6 was used to assist in the analysis of the environmental impacts, with the impact assessment method ReCiPe 2008. The system boundary of the study was expanded to take into consideration the effects caused by the consumption of coproducts generated within the two rice husk options. To make the options comparable, the functional units defined for both options were based on processing 1,000 tonnes of rice husk in both rice husk use systems studied. Results Based on the available data and assumptions made for this study, the results show that the use of rice husk in both electricity and cellulosic ethanol options had a significant effect in reducing the impacts on fossil fuel depletion and climate change, when compared with the conventional processes. However, the use of rice husk in both options caused a slightly higher impact on particulate matter formation than the conventional processes. The option of using rice husk to generate electricity was preferred over the option of using rice husk as a feedstock to produce cellulosic ethanol for all other impact categories analysed, except particulate matter formation, marine eutrophication, photochemical oxidant formation and freshwater ecotoxicity. In addition, it was found that using rice husk to produce cellulosic ethanol caused a considerably greater impact on human toxicity than its conventional product. Discussion The environmental benefits gained by using rice husk depend on the materials that rice husk is replacing. This means that the reduction of environmental impact depends upon the use of the rice husk. Conclusions Overall, the option of using rice husk to generate electricity shows benefits over the option of using rice husk to produce cellulosic ethanol for most impact categories analysed. However, the cellulosic ethanol option is better than the electricity option in terms of particulate matter formation, marine eutrophication, photochemical oxidant formation and freshwater ecotoxicity. Recommendations and perspectives In the short run, the option of using rice husk to generate electricity is more environmentally friendly than the option of using rice husk to produce cellulosic ethanol. However, if rice husk is to be used for electricity generation, the ash generated in power plants should be sent out to be used in other industries. It should not be disposed of in landfills as it causes greater impacts than other ash use options. In the time of oil shortages, rice husk should be considered for use as a feedstock to produce cellulosic ethanol for use as a substitute for petrol to help reduce the dependency of oil importation for Thailand. However, the production process of cellulosic ethanol should be improved to help increase efficiency in reducing the environmental impacts in other impact categories.
Keywords: Agricultural residue; Biofuel; Comparative LCA; Rice husk; System expansion; Waste management